Indonesian propolis suppressed the expression of COX-2 in inflamed rat dental pulp in direct capping treatment - Ardo Sabir (Journal of Dentomaxillofacial Science, 2019)
Objective: The aim of the present study ass to analysis the expression COX-2 on inflamed rat dental pulp after capped with propolis. Material and Methods: Propolis was obtained from South Sulawesi, Indonesia. Flavonoid and non-flavonoid were purified from an ethanolic extract of propolis (EEP). Eighty male Sprague Dawley rats were divided randomly into 5 groups, each group consisting of 16 rats. Group I as a negative control, rats were left without any treatment. A Class I cavity was prepared on the occlusal surface of permanent maxillary right first molar. Dental pulp was exposed and allowed in oral environment for 1 hour, then capping with EEP (group II), flavonoid propolis (group III), non-flavonoid propolis (group IV), or calcium hydroxide (Ca(OH)2) (group V). All cavities were filled with glass ionomer cement. The animals were sacrificed at 6 hours, 2, 4 or 7 days after treatment, biopsy samples were obtained, processed for immunostaining of COX-2 and viewed under light microscope. Data was statistically analyzed using Friedman and Kruskal-Wallis tests with significant level P<0.05. Results: Except in group I, COX-2 expression was decreased in all treatment group with the longer of observation time periods. In group II and group V, COX-2 expression was weaker than group III and IV at all periods time. However, there was no statistically significant differences of COX-2 expression among groups for each time period. Conclusions: The present study suggests that EEP and Ca(OH)2 were stronger than other materials test to suppressed COX-2 expression on inflamed rat dental pulp.